Desempeño laboral de la secretaria ejecutiva y su incidencia en la calidad de servicio a los usuarios del Banecuador (banco nacional de fomento) del Cantón Urdaneta Provincia de los Ríos. - Mackliff Veliz, Estefania Lisbeth (2016)
The quality of the service to users of BanEcuador del Cantón Urdaneta depends on the good work performance of the secretaries. The problem that currently exists in the Banana Bank (National Development Bank) of the Canton Urdaneta, lies in the quality of service to users, which is characterized by some secretaries and secretaries not performing in a competent manner the tasks entrusted to them, is attributed That among the main causes are in the limitation of the use of human relations and its advantages. This problem of poor work performance causes a deteriorating image to the company creating feelings of dissatisfaction among users, the secretary must meet certain characteristics that allow him to perform his duties with due professional efficiency. Banco Nacional de Fomento, currently called BanEcuador, is an autonomous development finance institution with private law and social and public purpose, this operation is based on the Organic Law, Statute, Regulations and Regulations.